2021
DOI: 10.1002/advs.202101526
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐Disguised Manganese Dioxide Nanoparticles for Neuroprotection by Reducing Oxidative Stress and Modulating Inflammatory Microenvironment in Acute Ischemic Stroke

Abstract: Reperfusion injury is still a major challenge that impedes neuronal survival in ischemic stroke. However, the current clinical treatments are remained on single pathological process, which are due to lack of comprehensive neuroprotective effects. Herein, a macrophage‐disguised honeycomb manganese dioxide (MnO 2 ) nanosphere loaded with fingolimod (FTY) is developed to salvage the ischemic penumbra. In particular, the biomimetic nanoparticles can accumulate actively in the damaged brain v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
124
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(124 citation statements)
references
References 51 publications
0
124
0
Order By: Relevance
“…The in vivo macrophage targeting of Cy5-siRNA-containing NCs was further explored via flow cytometry. In the early stage of reperfusion (several hours to several days after IR), pro-inflammatory M1-type macrophages occupy a greatly larger proportion than anti-inflammatory M2-type macrophages in the injured myocardium [ [58] , [59] , [60] , [61] ]. Thus, the proportion of M1-or M2-type macrophages in the injured heart and the internalization of Cy5-siRNA-containing NCs in them were monitored.…”
Section: Resultsmentioning
confidence: 99%
“…The in vivo macrophage targeting of Cy5-siRNA-containing NCs was further explored via flow cytometry. In the early stage of reperfusion (several hours to several days after IR), pro-inflammatory M1-type macrophages occupy a greatly larger proportion than anti-inflammatory M2-type macrophages in the injured myocardium [ [58] , [59] , [60] , [61] ]. Thus, the proportion of M1-or M2-type macrophages in the injured heart and the internalization of Cy5-siRNA-containing NCs in them were monitored.…”
Section: Resultsmentioning
confidence: 99%
“…Fingolimod-macrophage-disguised honeycomb MnO 2 nanoparticles reversed the brain pro-inflammatory microenvironment through consuming excessive H 2 O 2 and promoting M1 microglia switch to M2 phenotype. 424 Results from an ischemic stroke rat model and in vitro studies revealed that bioinspired melanin nanoparticles had excellent antioxidant effects. Apart from reducing oxidative stress, melanin nanoparticles reportedly play a role in alleviating the production of inflammatory factors.…”
Section: Nanoparticle-based Therapeutic Methods For Vascular Aging-re...mentioning
confidence: 99%
“…The typical process of isolating cellular vesicles consists of several steps ( Figure 1A ). Firstly, the parental cells are harvested and resuspended in a hypotonic buffer, rendering the cytoplasm swollen and susceptible to fragmentation by external forces ( 6 , 7 ). Then, if the cytoplasmic components are to be removed, cells usually need to undergo approximately five freeze-thawing cycles and dounce homogenization to release intracellular proteins ( 6 , 7 ).…”
Section: Manufacturing Of Cellular Vesicles For Cancer Immunotherapymentioning
confidence: 99%
“…Firstly, the parental cells are harvested and resuspended in a hypotonic buffer, rendering the cytoplasm swollen and susceptible to fragmentation by external forces ( 6 , 7 ). Then, if the cytoplasmic components are to be removed, cells usually need to undergo approximately five freeze-thawing cycles and dounce homogenization to release intracellular proteins ( 6 , 7 ). Next, cell membranes are separated from other cellular components by continuous high-speed or density gradient centrifugation.…”
Section: Manufacturing Of Cellular Vesicles For Cancer Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation